Distribution of transparent exopolymer particles (TEP) in distinct regions of the Southern Ocean - Zamanillo Campos, Marina; Ortega-Retuerta, E.; Nunes, Sdena; Estrada, Marta; Sala, M. Montserrat; Royer, S.-J.; López-Sandoval, Daffne; Emelianov, Mikhail; Vaqué, Dolors; Marrasé, Cèlia; Simó, Rafel (Science of The Total Environment, 2019)
13 pages, 7 figures, 2 tables, supplementary data https://doi.org/10.1016/j.scitotenv.2019.06.524 Transparent exopolymer particles (TEP) are an abundant class of suspended organic particles, mainly formed by polysaccharides, which play important roles in biogeochemical and ecological processes in the ocean. In this study we investigated horizontal and vertical TEP distributions (within the euphotic layer, including the upper surface) and their short-term variability along with a suite of environmental and biological variables in four distinct regions of the Southern Ocean. TEP concentrations in the surface (4 m) averaged 102.3 ± 40.4 μg XG eq. L and typically decreased with depth. Chlorophyll a (Chl a) concentration was a better predictor of TEP variability across the horizontal (R = 0.66, p < 0.001) and vertical (R = 0.74, p < 0.001) scales than prokaryotic heterotrophic abundance and production. Incubation experiments further confirmed the main role of phytoplankton as TEP producers. The highest surface TEP concentrations were found north of the South Orkney Islands (144.4 ± 21.7 μg XG eq. L), where the phytoplankton was dominated by cryptophytes and haptophytes; however, the highest TEP:Chl a ratios were found south of these islands (153.4 ± 29.8 μg XG eq (μg Chl a), compared to a mean of 79.3 ± 54.9 μg XG eq (μg Chl a) in the whole cruise, in association with haptophyte dominance, proximity of sea ice and high exposure to solar radiation. TEP were generally enriched in the upper surface (10 cm) respect to 4 m, despite a lack of biomass enrichment, suggesting either upward transport by positive buoyancy or bubble scavenging, or higher production at the upper surface by light stress or aggregation. TEP concentrations did not present any significant cyclic diel pattern. Altogether, our results suggest that photobiological stress, sea ice melt and turbulence add to phytoplankton productivity in driving TEP distribution across the Antarctic Peninsula area and Atlantic sector of the Southern Ocean This ...